Design approach of discrete-time resonant controllers for uninterruptible power supply applications through frequency response analysis - Carballo, Roberto Esteban (2016)
A new methodology to design discrete-time multiple resonant controllers for single-phase uninterruptible power supply inverters is proposed in this study. This methodology is based on classical linear tools and consists on the synthesis of the inverter output impedance according to standard specifications. This synthesis is performed using a multi-loop control strategy composed of an inner current control loop using a proportional controller, and an outer voltage control loop using the multiple resonant controller. A prototype was built to demonstrate the practical feasibility of the theoretical proposal. A significant reduction of the output impedance at determined harmonic frequencies resulted in a low-voltage total harmonic distortion of the output voltage of about 1.76%, for IEC 62040-3 reference non-linear load.